Impact of prolonged environmental exposure on stress transfer efficiency in poly(p‐phenylene terephthalamide)/epoxy composites. Issue 4 (11th January 2021) - Anagnostopoulos, George; Koukaras, Emmanuel N.; Parthenios, John; Galiotis, Costas
Abstract: The mechanical performance of fiber‐reinforced composites is seriously affected by their exposure to the environment. The combined action of elevated temperatures, humidity, and UV radiation (aging) on aramid fibers/epoxy resin composites is examined by employing Raman spectroscopy in tandem with mechanical loading. The imposed conditions drastically affect the interface of the composites altering the performance of the material under tensile loads. Although the maximum values of interfacial shear strength for the aged material are similar to that of the pristine material; however, they appear at lower strain levels, which is attributed to the significant decrease of the shear modulus of the epoxy matrix combined with the failure of aramid fibers to sustain the external loading due to the aging process. At high strains, the interface fails at lower strain levels (compared to the pristine sample) due to significant increase of micro‐cracking and micro‐voids on the surface of the aged composites. The formation of such flaws is the primary reason for the reduced mechanical performance and early failure of the composite material. Abstract :